Examining the Impact of Pedagogical Knowledge and Skills on Intermediate Phase Mathematics Teacher's Engagement in Chris Hani East Education District - Kumanda , Nomaroma; Baidoo, Joseph; Mutesasira, Godfrey; Bulelwa, Makena; Harry, Kasumba; Anthony Kambi, Masha; Wendy, Mashologu (Mathematics Education Journal, 2025)
This study examines the impact of pedagogical knowledge and skills on the engagement of intermediate-phase mathematics teachers in the Chris Hani East Education District, framed within the context of Self-Determination Theory. Given the critical role that effective teaching plays in student learning outcomes, understanding how teachers' pedagogical competencies influence their engagement is essential. Utilizing a qualitative research approach, data were collected through semi-structured interviews and focus group discussions with mathematics teachers. The findings reveal that teachers with strong pedagogical knowledge and skills are likelier to create positive learning environments that foster student engagement, aligning with the principles of autonomy and competence. Teachers lacking adequate instructional strategies reported challenges in maintaining student interest and participation. The study also identifies barriers such as insufficient resources, pressure to adhere to strict curricula, and a lack of confidence in teaching complex mathematical concepts. These insights underscore the need for targeted professional development programs that enhance teachers' pedagogical competencies, ultimately aiming to improve both teacher engagement and student learning outcomes in mathematics education. This research highlights the importance of equipping South African teachers with the necessary skills and knowledge to engage and inspire learners, thereby improving the overall learning experience.